KESULITAN LITERASI BACA TULIS PADA PESERTA DIDIK KELAS III SEKOLAH DASAR - Debi, Yolanda Putri; Eka Sastrawati; Hendra Budiono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Reading and writing literacy skills are fundamental abilities that must be instilled from the elementary school level, as they serve as the foundation for learning success across all subjects. This study aims to describe the difficulties in reading and writing literacy among third-grade elementary school students, the contributing factors, and the role of teachers in addressing these challenges. The research employed a descriptive qualitative method with a case study approach. The subjects were third-grade students of a public elementary school. Data were collected through observation, interviews, and documentation, while data analysis used the Miles & Huberman model, which includes data reduction, data display, and conclusion drawing. The findings revealed that some third-grade students still experienced difficulties in reading and writing, such as reading haltingly, spelling errors, difficulty identifying the main idea of a text, and mistakes in the use of capital letters and punctuation. The contributing factors included low reading interest, the influence of gadgets, limited family support, and irregular study habits. Teachers played a crucial role in providing guidance, motivation, and applying engaging teaching methods and media to help students overcome literacy difficulties.